The dead don't hurt [videorecording (DVD)] - Mortensen, Viggo, 1958- (Shout Factory, 2024)
Vivienne Le Coudy is a fiercely independent woman who embarks on a relationship with Danish immigrant Holger Olsen. After meeting Olsen in San Francisco, she agrees to travel with him to his home near the quiet town of Elk Flats, Nevada, where they start a life together. The outbreak of the civil war separates them when Olsen makes a fateful decision to fight for the Union. This leaves Vivienne to fend for herself in a place controlled by corrupt Mayor Rudolph Schiller and his unscrupulous business partner, powerful rancher Alfred Jeffries. Alfred's violent, wayward son Weston aggressively pursues Vivienne, who is determined to resist his unwanted advances. When Olsen returns from the war, he and Vivienne must confront and make peace with the person each has become. Both a tragic love story and a nuanced depiction of the conflict between revenge and forgiveness, The Dead Don't Hurt is a portrait of a passionate woman determined to stand up for herself in an unforgiving world dominated by ruthless men.